Electronic identity (eID) and electronic signature (eSig) for eGovernment services – a comparative legal study. Issue 1 (21st March 2016) - Lentner, Gabriel M.; Parycek, Peter
Abstract : Purpose: – This paper aims at providing an overview of different approaches toward identity management pertaining to citizen to government (C2G) eGovernment applications. Design/methodology/approach: – The paper adopts a comparative law methodology. It asks how different legal systems deal with the same problem. The different legal frameworks of Austria, Germany, Liechtenstein and the Swiss Canton of Zug are analyzed and compared pertaining to identification and authentication. The process of comparison involves three phases: the descriptive phase (describing and analyzing the legislation to be compared), the identification phase (identifying the differences and similarities between the systems compared) and the explanatory phase (attempting to explain the resemblances and similarities between the systems). Findings: – Each of the four countries adopted different legal solutions. This is due to the different legal culture and the existing legal framework in which the legislator, in most cases, seeks to fit in the respective eGovernment solution, rather than adopting a completely new solution. Originality/value: – This study reveals different possibilities for legislatures to regulate electronic C2G procedures, ranging from a combination of electronic identity (eID) and electronic signature to pragmatic eID models in combination with further electronic authentication functionalities. The focus of the study is the legal framework and not the technical solution.